Development of Learning Media in the Form of Electronic Books with Dynamic Electricity Teaching Materials - Perdana, Fengky Adie; Zakariah, Siti Hajar; Alasmari, Talal (Journal of Educational Technology and Learning Creativity, 2023)
Purpose of the study: This study aims to develop learning media in the form of electronic books with the subject matter of Dynamic Electricity for class X SMA semester II that meet the good criteria. Methodology: This development research uses research and development methods. The development model used in this study is a procedural model, namely a descriptive model that shows the steps that must be followed to produce a product in the form of learning media. Data obtained through interviews and questionnaires. The data analysis technique used is descriptive qualitative analysis. Main Findings: Based on data analysis in this study, it was concluded that the results of the development of electronic book media obtained very good criteria in terms of material and media aspects. Novelty/Originality of this study: Making and presenting electronic books as learning media in the form of digital media is done using the Corel Draw X4 and Kvisoft Flipbook Maker Pro 3.6.5 programs and then saving them in the .exe format.